Level of satisfaction of fishermen with services issuance of sailing approval letter (SPB) at PPS Kutaraja Banda Aceh - Elda Lestari Darsal; Muhammad Agam Thahir; Hafinuddin Hafinuddin; Nabila Ukhty (Universitas Teuku Umar, 2025)
The Sailing Approval Letter (SPB) is an important state-owned document issued at the fisheries syahbandar. This document is required when conducting fishing activities. SPB is issued through public services that aim to ensure the safety and security of fishermen when sailing. The purpose of this study is to determine the level of satisfaction of fishermen in the SPB issuance service and see what are the supporting factors and inhibiting factors in it. This research was conducted at Syahbandar PPS Kutarja in April 2025. The research method used is quantitative using Likert scale measurement, then analyzed descriptively. The results showed that the fishermen satisfaction index value at PPS Kutaraja was 88.70 with the Very Good category. The elements of service that need to be improved by syahbandar officers are: 1)handling complaints, suggestions and input, 2)product specifications of service types, and 3)executor behavior.